2018
DOI: 10.3389/fphar.2018.00944
|View full text |Cite
|
Sign up to set email alerts
|

Periplaneta americana Ameliorates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Rats by Keap1/Nrf-2 Activation, Intestinal Barrier Function, and Gut Microbiota Regulation

Abstract: Periplaneta americana, a magic medicinal insect being present for over 300 million years, exhibits desirable therapeutic outcome for gastrointestinal ulcer treatment. Nowadays, P. americana ethanol extract (PAE) has been shown to ameliorate ulcerative colitis (UC) by either single-use or in combination with other therapeutic agents in clinics. However, its underlying mechanisms are still seldom known. Herein, we investigated the anti-UC activity of PAE by alleviating intestinal inflammation and regulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 65 publications
1
49
1
Order By: Relevance
“…In addition, the beneficial effects of soy milk consumption on gut microbiota have been reported [58]; however, these effects have not been yet assessed in IBD patients. As recently stated, change in the gut microbiota has been a contributing factor to IBD incidence, particularly UC [59][60][61]. In addition, it has been shown that gut microbiota imbalance can affect disease symptoms [62].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the beneficial effects of soy milk consumption on gut microbiota have been reported [58]; however, these effects have not been yet assessed in IBD patients. As recently stated, change in the gut microbiota has been a contributing factor to IBD incidence, particularly UC [59][60][61]. In addition, it has been shown that gut microbiota imbalance can affect disease symptoms [62].…”
Section: Discussionmentioning
confidence: 96%
“…This finding confirms the systemic nature of chronic inflammation since blood metabolome reflects the major changes within the body including both host and microbiota metabolism. It has been previously shown that the acute and chronic DSS-treatment leads to a substantial change of the intestinal microflora [49,59,60], which is a result of the immune system activation, epithelial cell defense, and the host glycan landscape disruption [61][62][63][64]. At the same time, changes in the intestinal microbiota result in a different metabolic outcome and in the perturbation of the host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA are beneficial for bowel health, and lower concentrations of SCFA metabolites have been detected in patients with UC than in healthy controls, which contributes to a detrimental composition by modulating the colonic microbiota . In addition, treatment with Periplaneta americana ethanol extract ameliorates UC in rats and could correct the disturbance of gut microbiota—in particular, by promoting the growth of beneficial bacteria and improving intestinal immunity . The destruction of indigenous macrophages in the subepithelial layer of lamina propria may impair immunity against intestinal flora and lead to UC .…”
Section: Ecological Imbalance Of Intestinal Flora In Ucmentioning
confidence: 99%